Reform Through Rulemaking? - Richard L. Marcus (Washington University Law Quarterly, 2002)
During what has been called the “Golden Age of Rulemaking,” giants trod the soil of rulemaking. Drawing from the legacy of Jeremy Bentham, David Dudley Field, and Roscoe Pound, a small band of drafters created the Federal Rules of Civil Procedure in the late 1930s and changed the American procedural landscape. Their reforms included completing Field’s effort to bury technical pleading requirements and adopting a revolutionary set of discovery provisions. More recently, the federal rulemakers’ 1966 revision of the class action rule has had at least revolutionary consequences, sometimes in the teeth of what the rulemakers said they wanted it to do. Altogether, these giants are seen to have accomplished “a major triumph of law reform”5 that “transformed civil litigation [and] . . . reshaped civil procedure.” Beyond that, “they have influenced procedural thinking in every court in this land . . . and indeed have become part of the consciousness of lawyers, judges, and scholars who worry about and live with issues of judicial procedure." We are even told that they “became a means of transforming the modes of judging.” It is thus not surprising that these revolutionary changes have become the heart of the modern civil procedure course in law schools, so that most American law students start learning about how lawsuits are handled by studying them. After they graduate, they continue to labor in the shadow of these reforms. Most states have adopted procedural rule provisions that mirror the Federal Rules, and even in states that have persisted in alternative procedural provisions, the pleading, discovery, and class action innovations of the Federal Rules have made their mark. Although one can question whether there really was a causal relationship between rule changes and the transformation of litigation, given this experience, it is understandable that one familiar with the broad consensus that rulemaking worked such a change in the past would look now to rulemaking as the method for further reforms to address the challenges of 21st century litigation. However, as the diffidence in the title of this Article suggests, it is not at all clear that such reform can come from this source. Perhaps the pervasive and longstanding effect of the original Rules resulted from the intellectual capacity and fortitude of the federal rulemakers themselves. Charles Clark, at least, implied that self-confidence was central to the drafting effort he led as Reporter to the committee that produced the original Federal Rules when he urged that “reformers must follow their dream and leave compromises to others.” It is difficult to find similar confidence welling in the hearts of contemporary rulemakers. It is particularly difficult to find any enthusiasm for any undertaking that might be deemed “revolutionary,” or perhaps even aggressive. To the contrary, what one hears about rulemaking is that it is caught in a period of crisis. Reflecting on recent reform efforts, this paper therefore evaluates the prospects for future reform from this quarter. It begins by invoking three perspectives that might inform that inquiry and then elaborates on various themes of crisis that have been heard over the past twenty years. Against that background, it examines some features and episodes of recent rulemaking, partly from the perspective of an insider. Despite the pervasive and valid concerns about a crisis in rulemaking, it concludes that some modest reform is possible, and that rulemaking’s inability to deliver revolutionary change may not be a bad thing. Indeed, it may be that the latitude accorded the giants of rulemaking was something of an anomaly in American legal history.
Keywords: Law reform; Civil procedure; Civil law; Legal reform